Trade Facilitation Indicators The Potential Impact of Trade Facilitation on Developing Countries' Trade - Moïsé, Evdokia (OECD Trade Policy Papers, 2013)
This report presents the findings of the OECD indicators for assessing the impact of specific trade facilitation measures on developing countries' trade. Sixteen trade facilitation indicators (TFIs) have been constructed, corresponding to the main policy areas under negotiation at the WTO, with the aim to estimate the impact of addressing specific hurdles in the trade and border procedures of a given country. The policy areas that seem to have the greatest impact on trade volumes and trade costs not only for imports but also to export performance are the availability of trade-related information, the simplification and harmonization of documents, the streamlining of procedures and the use of automated processes. The combined effect of improvements in these areas is greater than the simple sum of the impact of individual measures, reaching almost 14.5% reduction of total trade costs for low income countries, 15.5% for lower middle income countries and 13.2% for upper middle income countries